Posterior transverse interarch discrepancy on HbE β thalassemia patients - Yuniar Zen; Loes D. Sjahruddin (Universitas Airlangga, 2011)
Background: One of the symptoms that often arises on thalassemia patients is disharmony dentofacial, class II skeletal malocclusion, as a result of the malrelation of maxilla and mandible. This malrelation can be affected by either maxillary bone position, dentoalveolar maxillary position, mandibular bone position, dentoalveolar mandibular position, or combinations of those components. Purpose: The study was aimed to examine whether there is posterior transverse interarch discrepancy on the HbE β thalassemia patients or not. Methods: This study is an observational research with cross-sectional design. The sample consisted of 33 HbE β thalassemia patients and 33 non-thalassemia patients as a control group aged 12-14 years. Lateral cephalogram was carried out and dental casts of maxillary and mandibular dental arches were also taken in all of those patients. Results: There was no difference between the maxillary intermolar width of the HbE β thalassemia patients and that of the normal ones, but the mandibular intermolar width of the HbE β thalassemia patients was significantly smaller than that of the normal ones. Beside that, posterior transverse interarch discrepancy of of the HbE β thalassemia patients was significantly greater than that of the normal ones, which showed great difference between maxillary and mandibular intermolar widths. Conclusion: Posterior transverse interarch discrepancy of the HbE β thalassemia patients was different from that of the normal ones. The dentofacial abnormalities on the HbE β thalassemia patients aged 12-14 years primarily was due to disporposional dentofacial growth in the vertical, sagittal, and transversal directions, especially in the posterior region. <span style="font-family: TribuneItalic;